Instructional Materials and Alternative Teaching Practices in Physical Education - Emy A. Morbo (Indonesian Journal of Educational Research and Technology, 2021)
In physical education (PE) learning, one of the main problems faced by PE teachers is the lack of facilities and equipment. Therefore, it is necessary to find a better solution to solve this problem. This study used a descriptive evaluative and comparative research design to determine the level of achievement of the context, input, process, and product evaluation components in the learning program. This research was conducted in 3 selected schools in the Maguindanao Division-1, Philippines. The results show that books are used "widely" by sports teachers and journals are used for printed materials while electronic journals are never used for non-print references. Furthermore, overhead projectors, fitness centers, lockers, kick pads, jumping pits, punching bags, megaphones, and signage are teaching materials that have never been used in the delivery of lessons by sports teachers, local material development and alternative games are rarely used by PE teachers. Sports teachers invite alumni to help with sporting activities, and they also tap old players to help in the basketball game even though they never use beeps but only whistle. The level of use of printed materials by schools differed significantly between schools. So are results with non-printed or electronic material. In addition, researchers suggest that schools provide additional and up-to-date sports books for teachers and students, and, schools should provide other teaching materials that will assist teachers in teaching in the classroom.